Optimalisasi Pengelolaan Homestay Melalui Pelatihan Aplikasi SIMBOK-KU Berbasis Website dan Android pada Masyarakat Desa Candirejo yang Tergabung di PT. Wimbo - Emik Rahayu; Izza Ulumuddin Ahmad Asshofi; Karis Widyatmoko; Ibnu Utomo Wahyu Mulyono; Imang Dapit Pamungkas; Dian Indriana Hapsari; Nurjanah Nurjanah (Journal of Social Responsibility Projects by Higher Education Forum, 2022)
The development of tourism has been progressing rapidly. Tourism has now spread to the countryside, where a tourist village can be found. A tourist village is a village that has unique and distinctive values. Homestays are one of the supporting facilities required for the development of tourist villages. But unfortunately, in homestay management there are many limitations, including mastery of technology. Technology itself has an important role because digital-based homestay management can further increase efficiency and integration in homestay management. Because of that, Dian Nuswantoro University partnered with PT Wimbo to design a homestay management information system called SIMBOK-KU. This system makes it easy to monitor reservations, payments, service standards, and even homestay customer satisfaction. On November 12, 2022, this system went live. This system is a solution to several obstacles encountered in website management, such as difficulties in dividing customers among homestay members, inability to fulfill cashless payments, difficulty verifying reservations and payments through travel agents, difficulties managing financial reports, and difficulties managing homestay service standards.